Die Rolle der indirekten Energiekosten im deutschen produzierenden Gewerbe - Andreas Löschel; Oliver Kaltenegger; Martin Baikowski (Wirtschaftsdienst, 2015)
Die Energiestückkosten sind für die Wettbewerbsfähigkeit der Unternehmen ein entscheidender Indikator im Zusammenhang mit der Energiewende. Dabei wurden bislang die indirekten Energiekosten vernachlässigt. Diese gewinnen aber immer mehr an Bedeutung. Die Berechnungsmethode zur Bestimmung der totalen Enegiestückkosten der Expertenkommission zum Monitoring-Prozess "Energie der Zukunft" wird hier vorgestellt. – – Real unit energy costs allow us to monitor the burden of energy costs on fi rms and to assess the competitiveness of industrial sectors. However, the indicator disregards "indirect" energy costs, which are embodied in non energy-related intermediate inputs for the production of goods and services. Total real unit energy costs also take into account these indirect energy costs, which play an increasingly important role over time. In fact, they are greater than the direct energy costs in the main sectors of German manufacturing. Therefore, rising energy prices are not only relevant to energy-intensive fi rms but also to firms that seem to be unaffected by high energy costs directly. Energy policy should take into account both cost categories, even though indirect energy costs are more diffi cult to assess and less controllable than direct energy costs.
Keywords: O14; Q48; 330